Soil Washing Methods for Effective Removal of Heavy Metal Contaminants - Chiu, Jian Chong; Gani, Paran (Tecno Scientifica Publishing, 2024)
Soil pollution caused by heavy metals from anthropogenic activities poses a significant environmental and health threat globally. Traditional remediation methods like solidification/stabilization have limitations, prompting the need for alternative techniques. Soil washing emerges as a promising approach, employing physical and chemical methods to effectively remove contaminants. This paper explores soil washing methods, focusing on sites contaminated with heavy metals such as zinc, lead, nickel, mercury, arsenic, copper, chromium, and cadmium, particularly influenced by military and industrial activities. Several techniques, including physical separation and chemical extraction, are discussed, which consider a few factors such as magnetism, density, size, and hydrophobicity to concentrate metal contaminants and solubilize soils. Physical separation targets particulate contaminants, while chemical extraction addresses non-detrital metals or soils with adsorbed ionic forms. The study also analyses field applications of soil washing systems and the implementation of remediation techniques. It emphasizes the need for innovative soil remediation strategies to mitigate the adverse effects of heavy metal contamination on soil quality and human health.